Profil Protein Isolat Bakteri Resisten Merkuri Dari Pertambangan Emas Rakyat Di Desa Pongkor, Bogor-Jawa Barat, Indonesia - Patricia Wahyu Irawati (Universitas Atma Jaya Yogyakarta, 2017)
Mercury pollution due to gold mining at Pongkor Village can threaten the life of organisms because mercury is toxic. Bioremediation can be considered to reduce mercury concentration in the water. The mercury-resistant bacteria can be isolated from the area and may be developed as mercury bioremediation agents. This study aims to isolate mercury-resistant bacteria, test their resistance to mercury, and conduct protein profile studies after mercury induction. The mercury-resistant bacteria were isolated from soil samples in the Pongkor Village gold mining area and the isolate resistance to HgCl2 was measured based on the Minimum Inhibitory Concentration (MIC) value. The protein profile was analyzed using SDS PAGE gel electrophoresis. The results showed that two of the most resistant bacterial isolates to mercury were HgP1 and HgP2 with MIC value was 575 ppm. The protein profile showed that mercury induced decreased protein synthesis under normal conditions and increased synthesis of one protein suspected to play a role in the mechanism of bacterial resistance to mercury.